1999
DOI: 10.1097/00005131-199902000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Avascular Necrosis of the Femoral Head After Intertrochanteric Fractures

Abstract: Avascular necrosis of the femoral head is an uncommon complication after intertrochanteric fractures. The pathogenesis is unknown, but in patients developing pain who have had intertrochanteric fractures, osteonecrosis should be included in the differential diagnosis, especially in cases with risk factors for osteonecrosis or a proximal intertrochanteric fracture line that perhaps disrupts the vascular anastomotic ring at the base of the femoral neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
0
23
0
2
Order By: Relevance
“…Radiografia pós-operatória na incidência em AP, com 12 meses de evolução, após reoperação com realização de artroplastia total hí-brida do quadril. do ao tipo de implante utilizado, pois o ponto de entrada do PFN ® é a ponta do grande trocanter, região que não coloca em risco a vascularização da cabeça do fêmur; além disso, existem alguns relatos de casos de necrose avascular da cabeça do fêmur associada a fraturas trocantéricas que foram submetidas a outros tipos de implantes, inclusive com placa-tubo tipo DHS ® e DCS ® , o que sugere que esta complicação deve resultar do trauma inicial que determinou a fratura (33)(34)(35)(36) (figuras 9 e 10).…”
Section: Discussionunclassified
“…Radiografia pós-operatória na incidência em AP, com 12 meses de evolução, após reoperação com realização de artroplastia total hí-brida do quadril. do ao tipo de implante utilizado, pois o ponto de entrada do PFN ® é a ponta do grande trocanter, região que não coloca em risco a vascularização da cabeça do fêmur; além disso, existem alguns relatos de casos de necrose avascular da cabeça do fêmur associada a fraturas trocantéricas que foram submetidas a outros tipos de implantes, inclusive com placa-tubo tipo DHS ® e DCS ® , o que sugere que esta complicação deve resultar do trauma inicial que determinou a fratura (33)(34)(35)(36) (figuras 9 e 10).…”
Section: Discussionunclassified
“…The pin or screw osteosynthesis is really mini-invasive surgery (Figs. [8][9][10][11][12]. Impaction of the fracture by hammering decreases the circulation to the femoral head [67].…”
Section: Osteosynthesis Considerationsmentioning
confidence: 99%
“…Three trials comparing a fixed nail plate (Jewett or McLaughlin) with the sliding hip screw (SHS) found an increased risk of fixation failure for fixed nail plates. The two trials comparing the Resistance Augmented Baixauli (RAB) plate [10] with the SHS had contrasting results, notably in terms of operative complications, fixation failure, and anatomical restoration. One trial comparing the Pugh nail and the SHS found no significant difference between implants.…”
Section: Fractures Of the Femoral Neck And Proximal Femurmentioning
confidence: 99%
See 2 more Smart Citations